Fahr’s syndrome and idiopathic hypoparathyroidism – A case report - Marinković, Dejan M; Dragović, Tamara; Kiković, Saša; Kuzmić Janković, Snežana; Đuran, Zorana; Hajduković, Zoran (Vojnosanitetski pregled, 2017)
Introduction. Fahr´s syndrome is a rare, slowly progressive, neurodegenerative disorder, characterised by extensive, bilateral, and symmetrical basal ganglia calcification. It is associated with neuropsychiatric manifestations and gradually progressive cognitive impairment. Fahr's syndrome is the secondary form of brain calcification that is caused by various metabolic, infectious, or degenerative diseases. Case report. We presented a middle-aged male with Fahr's syndrome due to primary idiopathic hypoparathyroidism. Clinical diagnosis was based on signs and symptoms of hypocalcemia, progressive neuropsychiatric illnesses, laboratory evidence of hypoparathyroidism, and radiological signs of calcifications in the basal ganglia. The patient improved after only a few days of intravenous rehydration and calcium substitution, followed by oral supplemental calcitriol. Conclusion. Timely recognition of idiopathic and iatrogenic hypoparathyroidism allows appropriate treatment that can prevent the development and clinical manifestations of Fahr´s syndrome and potentially slow its progression.
Keywords: hypoparathyroidism; comorbidity; diagnosis; differential; drug therapy; neurodegenerative diseases; calcinosis; basal ganglia